Three-dimensional modelling of human quadriceps femoris forces - Chiu, L. Z.; Daehlin, T. E. (Journal of Biomechanics, 2021)
Quadriceps intramuscular anatomy is typically described in two dimensions. However, anatomical descriptions indicate fascicles in the quadriceps may have a three-dimensional orientation. The purpose of this investigation was to quantify the maximum force generating capacity of the individual quadriceps` muscles in three dimensions. Muscle architectural parameters were obtained from three cadaver specimens (two female) and input into a geometry-based multiple fascicle muscle force model. Vastus lateralis, vastus medialis, and rectus femoris had partitions which could be defined based on differences in the sense and direction of fascicles between partitions. Vastus lateralis and rectus femoris were bipennate due to partitions sharing an aponeurosis. Vastus lateralis deep and superficial partitions exerted posterior- (maximum: -29 ± 5 N) and anterior-directed (maximum: 58 ± 15 N) forces on their shared distal aponeurosis. Rectus femoris medial and lateral partitions exerted medial- (maximum: -38 ± 17 N) and lateral-directed (maximum: 19 ± 12 N) forces on their shared proximal aponeurosis. All vastus medialis fascicles ran along the proximal-distal axis. However, fascicles arising near the lesser trochanter also ran along the superficial-deep axis, while fascicles arising from the linea aspera ran along the medial-lateral axis. Thus, vastus medialis could be divided into longus and oblique partitions. Due to the large pennation angle, vastus medialis oblique could exert maximum medial-directed (-219 ± 93 N) and proximal-directed (279 ± 168 N) forces at approximately -40° and -70° knee flexion, respectively, indicating dual roles for vastus medialis oblique dependent on knee flexion angle.